Deteksi Dini Gangguan Jiwa Dan Masalah Psikososial Dengan Menggunakan Self Reporting Qustioner (SRQ-29) - Larasuci Arini; Setiadi Syarli (Jurnal Keperawatan Muhammadiyah, 2020)
Introduction:Psychosocial problems and mental disorders become important issues to be a concern, in addition to the increasing world prevalence, including in Indonesia. The impact of psychosocial problems and mental disorders has a major effect on the productivity of individuals and families. Objective: This research is intended to conduct screening / early detection of psychosocial problems and mental disorders to prevent and overcome them in the Riau Islands, especially the city of Batam. Method: This study uses a descriptive design with a cross-sectional study approach. Random sampling with several respondents as many as 196 respondents. The instrument used was Self Reporting-29 (SRQ-29). The study was carried out during September 2019Results: The results found: anxiety and depression (28%), indications of the use of psychoactive substances (4%), psychotic disorders (21%), PTSD (32%) and no indicated disorders (15%). Based on this study, it was concluded that the most common Conclusion:Problems found were PTSD, anxiety and depression and psychotic disorders.With this study, active participation from all parties, government and stakeholders are expected. Early prevention and screening will be more effective and efficient in overcoming psychosocial problems and mental disorders in the community.